Acetabular labral tears: diagnosis and management. Issue 1 (February 2022) - Basheer, Sheba Zulaikha; Maher, Niall; Holton, Colin Stuart
Abstract: The acetabular labrum is an important component of a stable, long-lasting, and well-functioning hip joint, contributing to joint congruity, load distribution and stability. Increased use of high-resolution magnetic resonance imaging has led to an increase in the radiological identification of acetabular labral tears and other soft tissue pathologies within the hip joint. An acetabular labral tear is thought to defunction the labrum and thereby contribute to micro-instability and altered joint pressures. This may result in clinically significant disability and pain. This article aims to summarize current understanding of the anatomy and function of the acetabular labrum and discuss strategies for management of symptomatic acetabular labral tears.